Cost stickiness, absorbed slack and enterprise risks: Evidence from China. - Qian Binhua; Yang Boyuan (PLoS ONE)
This study delves into the complex domain of enterprise finance to explore the relationship between cost stickiness and enterprise risks, with a particular emphasis on the role of absorbed slack. Our analysis is based on a comprehensive examination of 3,177 Chinese listed enterprises over a period of ten years, from 2007 to 2022. The findings reveal that cost stickiness is a widespread phenomenon among Chinese listed enterprises, exhibiting variation across different industries. Notably, a strong positive correlation is identified between cost stickiness and enterprise risks, a correlation that remains consistent through various robustness tests, including indicator permutation, sample reconfiguration, and the resolution of endogeneity issues. The research further highlights the mediating effect of absorbed slack in the relationship between cost stickiness and enterprise risks. This study not only confirms the ubiquity of cost stickiness and its association with enterprise risks but also underscores the significant impact of absorbed slack. We offer a novel perspective on the interaction among cost stickiness, absorbed slack, and enterprise risks, providing valuable insights for enterprises aiming to enhance their risk management strategies. The conclusions and recommendations presented serve as a guide for those engaged in the challenging task of managing enterprise risks.